TINJAUAN HUKUM TERHADAP PERLINDUNGAN HAK ASASI MANUSIA ATAS DATA PRIBADI DALAM PENEGAKAN HUKUM DI ERA DIGITAL - Fransiskus, Nikola; Murary, Weron; Baho, Dayen (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Personal data is something that must be protected because it is actually everyone's right to privacy. The right to privacy is a human right and a constitutional right of citizens which has been regulated in the 1945 Constitution of the Republic of Indonesia. Providing protection for the right to privacy means also providing protection for the right to freedom of speech. This is also material in the Indonesian Constitution, the Constitution of the Republic of Indonesia, in Article 28F of the 1945 Constitution it is stated that the state guarantees the right of every person to communicate and obtain information to develop their personal and social environment, as well as the right to seek, obtain, own , store, process and convey information using all types of available channels. This formulation is the basis for granting digital rights to the community. The research method used in this writing is the normative legal research type. The type and source of data used is secondary data, and the data collection technique is by using secondary data or literature study, which means data collection is carried out by collecting data contained in books, documents, notes, reports. as well as statutory regulations relating to the object under study, then the data collected is then analyzed qualitatively.Research Results Legal protection for misuse of personal data can be carried out through prevention efforts, if existing regulations do not yet cover the system for misuse of personal data. Currently, personal data protection is contained in several laws and regulations, including: 1, Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008; 2, Government Regulation Number 82 of 2012.Keywords: Protection of human rigth, personal data, law enforcement in the digital era.